Solid holdup and circulation rate in a liquid-solid circulating fluidized bed with viscous liquid medium - Gnanasundaram, N.; Loganathan, M.; Perumal, Kumar (Brazilian Journal of Chemical Engineering, 2015)
Experiments were conducted in a liquid-solid circulating fluidized bed with different viscous liquids and particles to study the hydrodynamics, average solid hold up and solid circulation rate. The effects of operating parameters, i.e., primary liquid flow rate in the riser, auxiliary liquid flow rate, total liquid flow rate and viscosity of the liquid were studied for solids of different density and particle size. Results show that the circulating fluidization regime starts earlier for more viscous solutions because of the decrease in critical transitional velocity. The onset of solid holdup increases with an increase in liquid viscosity for sand and for glass beads. The solid circulation rate increases with an increase in total velocity and auxiliary velocity, and also increases with increasing viscosity.